Multi-Fresnel lenses pumping approach for improving high-power Nd:YAG solar laser beam quality - Liang, Dawei (2021)
These research projects (PTDC/FIS/103599/2008 and PTDC/FIS/122420/2010) were funded by the Science and Technology Foundation of Portuguese Ministry of Science, Technology and Higher Education (FCT-MCTES).